The Effect of Asphaltene on the Stability of Iraqi Water in Crude Oil Emulsions - Mohammed, Sawsan A.M.; Maan, Sally D. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
In the present work, asphaltenes and resins separated from emulsion samples collected from two Iraqi oil wells, Nafut Kana (Nk) and Basrah were used to study the emulsion stability. The effect of oil resins to asphaltene (R/A) ratio, pH of the aqueous phase, addition of paraffinic solvent (n-heptane), aromatic solvent (toluene), and blend of both (heptol) in various proportions on the stability of emulsions had been investigated. The conditions of experiments were specified as an agitation speed of 1000 rpm for 30 minutes, heating at 50 °C, and water content of 30%. The results showed that as the R/A ratio increases, the emulsion will be unstable and the amount of water separated from emulsion increases. It was noticed that the emulsion of Nk crude oil became more stable at basic pH range, and reached to completely stabilized emulsion at pH=12. Whereas Basrah emulsion was stable in both acidic and basic pH ranges. Results indicated that toluene gave a good solubility for asphaltene, and a higher water separation for both crude oil emulsions. A mathematical model to determine the kinetic constants that characterize the coalescence in the emulsions was also developed.